2003
DOI: 10.1175/1525-7541(2003)004<1220:aereia>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An Extreme Rainfall/Runoff Event in Arctic Alaska

Abstract: Rainfall-generated floods in the Arctic are rare and seldom documented. The authors were fortunate in July 1999 to monitor such a flood on the Upper Kuparuk River in response to a 50-h duration rainfall event that produced a watershed average in excess of 80 mm. Atmospheric conditions prevailed that allowed moist air to move northward over areas of little or no vertical relief from the North Pacific Ocean to the Arctic Ocean. Cyclogenesis occurred along the quasi-stationary front separating maritime and contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 18 publications
3
57
0
Order By: Relevance
“…Together, these results indicate the increasing importance of rainfall for flood generation. These findings are consistent with studies from Kane et al (2003) and Cunderlik and Ouarda (2009). Kane et al (2003) showed in the Upper Kuparuk River, Alaska that rainfall-generated runoff events produce flood magnitudes that can exceed by a factor of three of those generated by snowmelt.…”
Section: Shifting Hydrology and Hydrological Extremessupporting
confidence: 91%
See 3 more Smart Citations
“…Together, these results indicate the increasing importance of rainfall for flood generation. These findings are consistent with studies from Kane et al (2003) and Cunderlik and Ouarda (2009). Kane et al (2003) showed in the Upper Kuparuk River, Alaska that rainfall-generated runoff events produce flood magnitudes that can exceed by a factor of three of those generated by snowmelt.…”
Section: Shifting Hydrology and Hydrological Extremessupporting
confidence: 91%
“…These findings are consistent with studies from Kane et al (2003) and Cunderlik and Ouarda (2009). Kane et al (2003) showed in the Upper Kuparuk River, Alaska that rainfall-generated runoff events produce flood magnitudes that can exceed by a factor of three of those generated by snowmelt. They concluded that the likelihood of major rainfall-generated floods is especially prevalent in catchments with limited soil storage and steep topography.…”
Section: Shifting Hydrology and Hydrological Extremessupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, peak discharge in small headwater streams, such as the upper Kuparuk, is less predictable. There is a peak in discharge during the spring thaw, but often, large storm events later in the summer produce comparable or even larger peaks in discharge (Kane et al 2003(Kane et al , 2008.…”
Section: Study Areamentioning
confidence: 99%